Teaching about gender diversity : teacher-tested lesson plans for K-12 classrooms / edited by Susan W. Woolley and Lee Airton. - Woolley, Susan W., 1977-; Airton, Lee (Canadian Scholars, 2020)
"Teaching about Gender Diversity is a collection of lesson plans that provide K-12 teachers in North America with the resources and tools to implement gender-inclusive practices, fully integrate gender diversity into their curriculum, and talk to students about gender. Authored by teachers who have direct experience teaching about gender diversity, this collection aims to help pre- and in-service teachers at all stages of comfort and confidence enhance their curriculum development skills in order to foster a classroom that welcomes all possible ways of living gender. The lesson plans unpack gender terminology, gender stereotypes, and the social construction of binary gender. Lessons range from read-alouds with early literacy picture books to creating a fanzine using visual arts, from engaging mathematics in the study of gender-neutral pronoun usage to developing a character's gender identity in a dramaturgical study. "--